Using shape and size to quantify variation in footprints for individual identification: Case study with white rhinoceros (Ceratotherium simum). (30th April 2013) - Law, Peter R.; Jewell, Zoe; Alibhai, Sky
Abstract For those vertebrate species that create sufficiently complex footprints, identifying individuals from their footprints promises to be a noninvasive technique of great potential for wildlife studies and conservation, but with statistical challenges. Various approaches to employing footprints for identification appear in the literature, but doubt often remains as to the information contained in the footprints and therefore of the reliability of the procedures. For footprints represented by landmarks, we propose using pre‐assigned measures of shape and size of configurations of landmarks to quantify the variation in footprints amongst individuals relative to the variation in each individual's footprints. Our method provides a relatively simple means of assessing when footprints (represented by landmarks) from individuals of a population will be useful for identifying individuals, independent of any particular identification algorithm, and is also a tool for exploring footprint landmark data to aid development of discrimination routines. We illustrate the method using footprints collected from a population of white rhinoceros (Ceratotherium simum) at Otjiwa Game Ranch, Namibia, during late 1999. © 2013 The Wildlife Society.